Penerapan Therapeutic Positions terhadap Parameter Vital Signs Pasien Stroke di Rumah Sakit Pusat Otak Nasional Prof. Dr. Dr. Mahar Mardjono Jakarta - Irman, Irman; Kariasa, I Made; Nova, Prima Agustia; Mulyatsih, MG Enny (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT This study aims to determine the application of therapeutic positions to the vital signs parameters of stroke patients at the Prof. Dr. National Brain Center Hospital. Dr. Mahar Mardjono Jakarta. This research is an application of Evidence-Based Nursing which was applied to 12 respondents. Each patient in the study group was positioned in various therapeutic positions every 2 hours following a semi-fowler's rotating schedule, lying on their side to the healthy side (Unaffected Side Position), lying on their back (Supine Position), and lying on their side to the side with hemiparesis or hemiplegia (Affected Side Position). Based on the results, the average systolic blood pressure decreased on the second post-intervention day (day 2) with a mean of 124.08 and a standard deviation of 3,147, while the diastolic mean was not much different from the first day, namely 83.17 and a standard deviation of 2,657. The average heart rate on the second-day post-intervention decreased with a mean of 84.92 and a standard deviation of 0.900. In the respiration rate variable, the decrease in the mean value post-intervention on the second day was 15.33 (standard deviation 0.888). The mean value for oxygen saturation levels (SPO2) with the mean post-test value on the second day was 99.75 (standard deviation 0.452). So it can be concluded that providing therapeutic positions intervention can reduce blood pressure, heart rate, and respiration rate and increase oxygen saturation. Keywords: Therapeutic Positions, Vital Signs  ABSTRAK Penelitian ini bertujuan untuk mengetahui Penerapan Therapeutic Positions Terhadap Parameter Vital Signs Pasien Stroke Di Rumah Sakit Pusat Otak Nasional Prof Dr. dr. Mahar Mardjono Jakarta. Penelitian ini merupakan Penerapan Evidence-Based Nursing yang diterapkan pada 12 responden. Setiap pasien dalam kelompok studi diposisikan pada berbagai posisi terapeutik setiap 2 jam dengan mengikuti jadwal berputar seperti semi fowler's, berbaring miring ke sisi yang sehat (Unaffected Side Position), berbaring terlentang (Supine Position) dan berbaring miring ke sisi yang hemiparesis atau hemiplegia (Affected Side Position). Berdasarkan hasil bahwa rata-rata tekanan darah sistole terjadi penurunan pada post intervensi hari kedua (day 2) dengan mean 124.08 dan standar deviasi 3.147, sedangkan diastole diperoleh mean yang tidak berbeda jauh dengan hari pertama yaitu 83.17 dan standar deviasi 2.657. Rata-rata heart rate post intervensi hari kedua terjadi penurunan dengan mean 84.92 dan standar deviasi 0.900. Pada variabel respiration rate diperoleh penurunan untuk nilai mean post intervensi hari kedua adalah 15.33 (standar deviasi 0.888). Nilai mean pada kadar saturasi oksigen (SPO2) dengan nilai mean post-test hari kedua 99.75 (standar deviasi 0.452). Pemberian intervensi therapeutic positions dapat menurunkan tekanan darah, heart rate, respiration rate dan meningkatkan saturasi oksigen. Kata Kunci: Posisi Terapeutik, Tanda-Tanda Vital